Effect of sulfur on the glass-forming ability, phase transformation, and thermal stability of Cu-Zr-Al bulk metallic glass. (15th June 2021) - Jiang, Hao-Ran; Hu, Jing-Yi; Neuber, Nico; Bochtler, Benedikt; Adam, Bastian; Riegler, Sascha S.; Frey, Maximilian; Ruschel, Lucas; Lu, Wen-Fei; Feng, Ai-Han; Busch, Ralf; Shen, Jun
Abstract: The effects of minor sulfur addition on the glass-forming ability (GFA), phase formation, thermal stability, and mechanical properties of the Cu47.5 Zr45.1 Al7.4 bulk metallic glass (BMG) were studied by conventional X-ray diffraction (XRD), in-situ high-energy synchrotron XRD, calorimetry, thermomechanical analysis, and scanning electron microscopy. Results show that sulfur has positive and negative effects on the GFA and thermal stability of Cu-Zr-Al alloys. On the one hand, sulfur can slow down the liquid dynamics, thus inhibiting the precipitation of eutectic phases during casting from the melt and heating from the as-cast glass, and hence favoring the glass formation and thermal stability of the sulfur-bearing alloys. On the other hand, the addition of sulfur promotes the formation of an Al-rich τ3 phase, which easily precipitates and is therefore catastrophic for the GFA and melt stability. The two factors compete with each other and ultimately lead to an optimal sulfur content of 0.75 at.% for the investigated Cu-Zr-Al alloys. Compared with the base alloy, this novel sulfur-containing BMG possesses improved GFA, enlarged supercooled liquid region, and comparable mechanical strength and toughness, making it a promising candidate for industrial applications as structural material. Furthermore, the schematics of the change in time–temperature–transformation diagrams with increasing sulfur concentration were proposed on the basis of experimental results. Graphical abstract: Image, graphical abstract